2015
DOI: 10.1007/s10826-015-0269-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Maltreating and Foster Families in Italy

Abstract: Maltreating and foster families belong to different research areas and have rarely been considered together. This exploratory study compared maltreating and foster families to demonstrate an integrated approach that overcomes the dichotomic view that often separates problematic families from those who have resources. This study had 81 participants: 48 maltreating parents and 33 foster parents and the children who were in foster care. We examined family functioning (FES), adult attachment styles (ASQ) and foste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Wiehe (2003) found that abusive parents exhibit lower empathy (perspective taking and empathic concern) relative to foster parents, as well as less self-confidence and less impulse control. These results have been repeatedly supported (e.g., Migliorini et al, 2016;Moed et al, 2017). Wiehe's (2003) findings also support self-efficacy as a foundation for supportive parenting.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 57%
“…Wiehe (2003) found that abusive parents exhibit lower empathy (perspective taking and empathic concern) relative to foster parents, as well as less self-confidence and less impulse control. These results have been repeatedly supported (e.g., Migliorini et al, 2016;Moed et al, 2017). Wiehe's (2003) findings also support self-efficacy as a foundation for supportive parenting.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 57%
“…Health and adaptation to changes are developed and are influenced by family relationships, especially in early childhood (Bornstein, 2006). Healthy family contexts are able to support children's growth, while families with multiple problems, including maltreatment, foster fragile and vulnerable family environments that do not allow for adequate psychological growth, and lead to repercussions in adult life (Migliorini, Rania, Cavanna, et al, 2015). Therefore, a family can be a protective factor or an environment of fragility that affects the health of its members (Cicchetti, 2013;Masten & Monn, 2015).…”
Section: Family Well-being and Parentingmentioning
confidence: 99%
“…We know that political participation is lower for women compared to men; this difference is attenuated if we look at the social involvement, because women prefer a social commitment rooted in the local boundaries (Onyx & Leonard, 2000). Another differences showing a gender difference is related to the type of social/political involvement; women prefer to be involved in direct care and less in public/ political activities (Wilson, 2000;De Piccoli & Rollero, 2010), confirming that women play a major role in care tasks not only in the family (Ferree, 2010;Migliorini, Rania, Cardinali, Guiducci, & Cavanna, 2015;Rania, Migliorini, Rebora, & Cardinali, 2015) but also in relationships with the contexts and the community. In particular, in the promotion and prevention at the community level, the role of Running head: GENDER PERSPECTIVE AS PROMOTION OF WELL-BEING AND HEALTH women is crucial for the well-being of the community (i.e.…”
mentioning
confidence: 87%